A Model of FPGA-based Direct Torque Controller - Tole Sutikno; Nik Rumzi Nik Idris; Aiman Zakwan Jidin; Auzani Jidin (Institute of Advanced Engineering and Science, 2013)
This paper presents a generic model of a fully FPGA-based direct torque controller. This model is developed using two’s-complement fixed-point format approaches, in register-transfer-level (RTL) VHDL abstraction for minimizing calculation errors and consuming hardware resource usage. Therefore, the model is universal and can be implemented for all FPGA types. The model is prepared for fast computation, without using of CORDIC algorithm, a soft-core CPU, a transformation from Cartesian-to-polar coordinates, and without the help of third-party applications. To get simpler implementation and fast computation, several methods were introduced: i) the backward-Euler approach to calculate the discrete-integration operation of stator flux, ii) the modified non-restoring method to calculate complicated square-root operation of stator flux, iii) a new sector analysis method. The design, which was coded in synthesizable VHDL in RTL abstraction for implementation on Altera DE2-board has produced very-precise calculations, with minimal error when being compared to MATLAB/Simulink double-precision calculation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2002